2019
DOI: 10.1016/j.fertnstert.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial microbiota in infertile women with and without chronic endometritis as diagnosed using a quantitative and reference range-based method

Abstract: Objective: To systematically compare the endometrial microbiota in infertile women with and without chronic endometritis (CE), as diagnosed by a quantitative and reference range-based method. Design: Case-control observational study. Setting: University-affiliated hospital. Patient(s): One hundred and thirty infertile women. Intervention(s): Endometrial biopsy and fluid (uterine lavage, UL) collected precisely 7 days after LH surge, with plasma cell density (PCD) determined based on Syndecan-1 (CD138)-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 53 publications
1
70
2
2
Order By: Relevance
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
“…Alteromonas [16], Anaerococcus [15], Atopobium [15], Bifidobacterium [14][15][16], Dialister [15], Gardnerella [14][15][16], Lactobacillus [14,16], Magasphaera [14], Parvimonas [14], Prevotella [14,15], Propionibacterium [14], Streptococcus [14,16], Veillonella [14] Endometrial polyps Alteromonas [16], Bifidobacterium [16], Euryarchaeota (Archaea) [16], Gardnerella [16], Lactobacillus [16], Streptococcus [16] Dysfunctional menstrual bleeding Gardnerella [22], Lactobacillus [22], Prevotella [22], Sneathia [22], Veilonella [22] Endometrial cancer…”
Section: Healthymentioning
confidence: 99%
See 2 more Smart Citations
“…However, given that only 16S methodology was used it is unclear whether certain species or subspecies of Lactobacillus may be capable of conferring this benefit. A recent study on the endometrial microbiota and chronic endometritis reported that Lactobacillus crispatus was less abundant in patients with CE suggesting that there may be certain Lactobacillus spp that is protective (27). More comprehensive whole genome shotgun sequencing (WGS) may help answer this question.…”
Section: Normal Microbiome Uterine Microbiomementioning
confidence: 99%